Demonstrasi dan Sosialisasi Pembuatan Spray Anti Nyamuk Berbahan Dasar Sereh dan Kulit Lemon Sebagai Upaya Pencegahan Penyakit Demam Berdarah - Adhin Al Kasanah; Binar Wahyuning Widhi; Yudha Vika Diliyana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Background: Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia. DHF prevention can be achieved through mosquito vector control. The use of plant-based natural mosquito repellents is a safe, affordable, and environmentally friendly alternative. Lemongrass (Cymbopogon citratus) and lemon peel (Citrus limon) contain active compounds with potential mosquito-repellent properties. Objective: This community service activity aimed to improve community knowledge and skills in DHF prevention through the demonstration and socialization of making mosquito repellent spray from lemongrass and lemon peel. Methods: The activity was conducted using socialization, health education, demonstration, and hands-on practice methods. Participants received education regarding DHF, the benefits of natural mosquito repellents, and training on how to prepare mosquito repellent spray made from lemongrass and lemon peel. Evaluation was carried out using pre-tests and post-tests to measure improvements in knowledge, as well as observation of participants’ skills in independently producing the spray. Results: The results showed an increase in participants’ knowledge, indicated by an improvement in the average score from 55 on the pre-test to 85 on the post-test. All participants were able to independently produce mosquito repellent spray according to the demonstrated procedures. Participants also showed high enthusiasm throughout the activity and gained an understanding of the benefits of utilizing natural ingredients as an alternative approach to preventing mosquito bites that may cause DHF.